Internet Bondholder Relations: Explaining Differences in Transparency among German Issuers of Corporate Bonds - Heinrich Degenhart; Steve Janner (Kredit und Kapital, 2012)
Internet Bondholder Relations: Explaining Differences in Transparency among German Issuers of Corporate Bonds Bondholder relations gains importance for German non-financial firms as the debt market environment is changing significantly. Beyond an unprecedented increase in the amount of outstanding securities, there are two other effects that we observe in the German market for corporate bonds: an increasing focus on retail investors and a growing number of small to medium-sized firms entering the market. Both developments underline the need to explore bondholder relations, its implementation and effectiveness. In the course of this study, we intend to promote the understanding of why some firms disclose more to their bondholders than others. Following the information, agency, and related frameworks, we assume that Internet financial reporting helps reduce information asymmetries between bond issuers and dispersed investors. We devote this study to identifying main factors that determine cross-sectional heterogeneity. Conducting a multivariate analysis, we test hypotheses on the influence of capital market orientation, investors' informational needs, firm complexity, default risk, and family ownership. We find that all constructs, except for the default risk, are at least partly relevant in explaining the extent of information that bond issuers disclose on their websites. (JEL D82) – – Anleihekommunikation über das Internet: Ansatz zur Deutung von Unterschieden zwischen deutschen Emittenten von Unternehmensanleihen Das Thema der Anleihekommunikation ist für viele deutsche Nichtfinanzunternehmen eine Aufgabe, die infolge der gegenwärtigen Marktveränderungen stark an Bedeutung gewonnen hat. Neben einem ansteigenden Gesamtvolumen an Unternehmensanleihen können vor allem eine Integration von Privatinvestoren in den Kreis der Anlegerzielgruppe sowie eine verstärkte Kapitalorientierung mittelständischer Unternehmen beobachtet werden. Diese Entwicklungen unterstreichen den Bedarf, die Anleihekommunikation, ihre Umsetzung und Wirksamkeit zu untersuchen. Im Rahmen dieser Studie beabsichtigen wir, einen Erklärungsbeitrag zur grundlegenden Frage zu leisten, warum einige Unternehmen offener gegenüber dem Anleihenmarkt sind als andere. Den Implikationen der Prinzipal-Agentenund angrenzenden Theorien folgend nehmen wir an, dass Onlinefinanzberichterstattung die Informationsasymmetrien zwischen Anleiheemittenten und anonymen Kapitalmarktteilnehmern zu verringern vermag. Wir führen diese Studie durch, um wesentliche Faktoren zu identifizieren, die Querschnittsvarianzen erklären können. Mittels einer multivariaten Analyse testen wir verschiedene Hypothesen zum Einfluss der Kapitalmarktorientierung, Informationsbedürfnisse von Investoren, Unternehmenskomplexität, des Bonitätsrisikos sowie der Familieneigentümerschaft. Dabei stellen wir fest, dass – außer dem Bonitätsrisiko – sämtliche dieser Konstrukte zumindest teilweise einen signifikanten Einfluss haben.
Keywords: D82; 330